Influence of Normal Tissue Objective Tools on Treatment Planning System in Nasopharyngeal Carcinoma (NPC): A 3D Printed Anthropomorphic Phantom Study - Ivory Noersjafrudin; Ulfi Hanum; Asmaul Marufah; Aloysius Putranto; Endarko Endarko (Iranian Journal of Medical Physics)
Introduction: The normal tissue objective (NTO), one of the new aspects in the radiation treatment planning system (TPS), aims to lower the absorbed dose received by organs at risk (OARs) close to the target volume or Planning Target Volume (PTV). This study was conducted to ascertain the impact of planning in nasopharyngeal cancer (NPC) cases both with and without manual NTO settings.Material and Methods: The study used a 3D printed head and neck phantom exposed to radiation using the Intensity Modulated Radiation Therapy (IMRT) technique with 6000 cGy prescribed dose and divided into 30 fractions to find the discrepancies between the manually calculated absorbed dose and the automatic calculated absorbed dose of TPS. Moreover, evaluation parameter indicators, including the homogeneity index (HI), conformity index (CI), gradient index (GI), and comprehensive quality index (CQI), were used to make comparisons. NTO parameter used in manual plans are f0 = 107%, f∞ = 65%, dose fall-off  = 0.05 mm-1, and xstart = 0.75 cm.Results: The statistical analysis resulted in a significant difference between the calculated absorbed dose and TPS's absorbed dose of Automatic NTO and Manual NTO, whereas, Without NTO plans, there was no statistical difference. The HI values for Automatic NTO, Manual NTO, and Without NTO are 0.118, 0.05 , and 0.053, respectively. The CI values for Automatic NTO, Manual NTO, and Without NTO are 0.91, 0.99, and 0,19. The GI value for Automatic NTO, Manual NTO, and Without NTO are 3.34, 4.94, and 7.29, respectively. CQI parameter showed that the Automatic NTO plan performs better than the Manual NTO plan based on the maximum dose received by the OAR.Conclusion: In this study, the manual NTO plan showed better performance by reducing hot spots in the central region of PTV.